SOCIAL AND PEDAGOGICAL WORK WITH CHILDREN AT RISK BY MEANS OF ART THERAPY (DANCE) - Burenina, Svetlana; Kalinina, Svetlana; Petrash, Elena; Borisov, Boris; Shpak, Alexey (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
This article is devoted to the problems of social and pedagogical support for children of the "risk group". The purpose of the article is to study the potential of using dance as a direction of art therapy in social and pedagogical work with children of the "risk group". Research tasks were solved using the provisions of personality-oriented, anthropological, facilitation and integrated approaches. The program of art therapy developed by us through dance has shown its effectiveness: adolescents have increased motivation for creativity; improved data on the socio-psychological climate, and also increased the number of adolescents with a high level of confident behavior.